PENDIDIKAN AGAMA ISLAM SEBAGAI FONDASI PEMBENTUKAN KARAKTER BANGSA BERKEMAJUAN - Sadiyah, Sadiyah (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2017)
The existence of Islamic religion education in Indonesia from the early period has raised dilemmatic discussion, it appears many political policies on the existence of religion education. This present article shows the universality of Islamic-character concepts in preparing a generation to face global concepts. Through education, Islamic concepts can be internalized in students’ mind. The processes will, hopefully, have resulted not only firm understanding but also resourceful actions in daily activities. When it has achieved, the students can make contribution to personal, social, and national development.